VERIFICATION OF SEASONAL PREDICTION USING CONSTRUCTED ANALOGUE METHOD FOR WATER AVAILABILITY ON MAIZE CROP (Case Study: Garut Regency, West Java) - HANIF AFFAN YUSRON (NIM : 12813034), MUHAMMAD
Maize crop is considered as a strategic agricultural commodity. West Java Province is one of the national maize production centers, with the main location of the producers is Garut Regency. However, maize crop is sensitive to climate variability. Thus, it is important to make seasonal predictions of maize water balance in Garut Regency. In this study, the method used for seasonal prediction is Constructed Analogue (CA). Verification is required on this prediction to acquire its skill before being performed operationally. In this study, the output of Climate Forecast System version 2 (CFSv2) model is downscaled using CA method. The predictors are stream function (ψ) and velocity potential (χ) at 850 hPa level, whereas the predictand is rainfall. The predicted rainfall is then processed into effective rainfall which will be used along with evapotranspiration of maize crop to calculate the maize water balance. The predicted water balance is verified using Brier score, Brier skill score, and reliability diagram. Prediction of maize water balance surplus using CA method has good accuracy and skill in planting period 1 (November Ã‚Â– February), 2 (March Ã‚Â– June), and 3 (July Ã‚Â– October). The prediction of maize water balance deficit tends to have low accuracy and no skill in planting period 2, but has moderate accuracy and low skill in planting period 3. The reliability of maize water balance surplus and deficit prediction in planting period 2 and 3 is classified as marginally useful for decision-making. The accuracy and skill difference between prediction of maize water balance from lead-1 season and lead-2 season is not significant.